2003
DOI: 10.1536/jhj.44.713
|View full text |Cite
|
Sign up to set email alerts
|

<b>Cyclic GMP Production by ANP, BNP, and NO during Worsening and Improvement of Chronic Heart Failure</b>

Abstract: SUMMARYCyclic GMP (cGMP) serves as an intracellular second messenger of atrial natriuretic peptide (ANP), brain natriuretic peptide (BNP), and nitric oxide (NO) and its peripheral blood concentration is an index of its biological activity. It has been reported that the plasma concentration of cGMP is correlated with the concentrations of ANP and BNP and is related to the prognosis of chronic heart failure patients, but the relation with NO has not been studied. Therefore, we investigated the roles of ANP, BNP,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 23 publications
(21 reference statements)
1
13
1
Order By: Relevance
“…8, 28 Plasma ANP and BNP levels were significantly elevated at terminal Stage D HF corresponding to 20 weeks. Consistent with clinical reports for overt HF 15, 20, 29 cGMP levels were elevated at Stage C and D of HF in DCM. While plasma cGMP levels are positively associated with plasma immunoreactive ANP or BNP, NP system activation appears insufficient to attenuate the decline in systolic function and transition to terminal HF.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…8, 28 Plasma ANP and BNP levels were significantly elevated at terminal Stage D HF corresponding to 20 weeks. Consistent with clinical reports for overt HF 15, 20, 29 cGMP levels were elevated at Stage C and D of HF in DCM. While plasma cGMP levels are positively associated with plasma immunoreactive ANP or BNP, NP system activation appears insufficient to attenuate the decline in systolic function and transition to terminal HF.…”
Section: Discussionsupporting
confidence: 89%
“…NP signaling is an important, but not sole determinant of circulating cGMP. 29 cGMP is an intracellular second messenger for nitric oxide (NO) 30 which is also elevated in chronic human HF. 29 It has been suggested that cGMP is produced mainly by NO in humans with chronic HF requiring hospitalization, but as HF improves and the patient nears discharge, NO is primarily produced by ANP and BNP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the severity of heart failure is linked to levels of ANP-related peptides 3436 . While patients with severe heart failure develop high levels of ANP-related peptides and high levels of cGMP, our study and others have shown that there is no correlation between cGMP levels and total ANP-related peptides 5, 37 . We postulated that one explanation for the loss of the relationship between levels of ANP-related peptides and cGMP could be that corin levels and pro-ANP cleavage were reduced in severe heart failure.…”
Section: Discussioncontrasting
confidence: 68%
“…Plasma cGMP, which is produced by activation of NPR-A and its cGMP cyclase, is a useful biomarker, reflecting the biological activity of ANP and BNP in vivo. In a study of patients with acutely decompensated HF, iANP and iBNP were shown to increase significantly as symptoms worsened and to decrease as symptoms resolved 33. However, cGMP levels at the worsening and improving phases remained unchanged.…”
Section: Clinical Implications Of Molecular Forms Of Natriuretic Peptmentioning
confidence: 96%